2014
DOI: 10.1007/s00044-014-1255-y
|View full text |Cite
|
Sign up to set email alerts
|

Design, synthesis, biological evaluation and toxicity studies of N,N-disubstituted biguanides as quorum sensing inhibitors

Abstract: A series of novel N,N-disubstituted biguanides (8a-8j) have been synthesized using varied secondary amines and cyanoguanidine under microwave irradiation. All the synthesized compounds were evaluated for quorum sensing inhibition (QSI) activity using Chromobacterium violaceum (ATCC12472)-based bioassay. Out of these ten compounds, two compounds 8a and 8g (IC 50 = 179 and 120 lM) showed maximum QSI activity. Decrease in violacein production was observed in the range of 0.2-200 lM concentration for these respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 60 publications
1
17
0
Order By: Relevance
“…As mentioned earlier, both of the assayed traits are under the control of QS. 20 , 21 Interestingly, we found that albendazole has anti-QS activities in sub-MICs in a dose-dependent manner. Therefore, it can inhibit violacein production in C. violaceum .…”
Section: Introductionmentioning
confidence: 77%
See 2 more Smart Citations
“…As mentioned earlier, both of the assayed traits are under the control of QS. 20 , 21 Interestingly, we found that albendazole has anti-QS activities in sub-MICs in a dose-dependent manner. Therefore, it can inhibit violacein production in C. violaceum .…”
Section: Introductionmentioning
confidence: 77%
“…This finding is also noticed by us in the previous study where N,N -disubstituted biguanides with aryl groups have shown a significant correlation between π stacking ability and observed biological activity. 21 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reaction was completed within 15 minutes with a clean conversion and good yields (86-89%). Similar conditions were used by Singh et al to afford N 1 ,N 1 -dialkylbiguanides (Scheme 7B) [23]. While the authors observed a remarkable rate acceleration of several orders of magnitude over conventional heating, little was understood about the role of microwaves on this specific conversion, i.e., thermal or non-thermal effects.…”
Section: Methodsmentioning
confidence: 78%
“…Compound 10 l was considered as a novel quorum sensing inhibitor. Moreover, a series of N , N ‐disubstituted biguanides as quorum sensing inhibitors have been synthesized . Among them, three N , N ‐disubstituted biguanides analogues could inhibit 20%‐50% violacein production of C. violaceum ATCC 12472 at 0.2 mM.…”
Section: Quorum Sensing Inhibitory Activitymentioning
confidence: 99%